2013
DOI: 10.1111/bjc.12016
|View full text |Cite
|
Sign up to set email alerts
|

The association between obsessive compulsive disorder and obsessive compulsive personality disorder: Prevalence and clinical presentation

Abstract: There may have been a sampling issue, as the study compared patients from a specialist clinic for the treatment of OCD and Panic disorder. Furthermore, OCD referrals were primary, secondary, or tertiary, whereas Panic disorder referrals were primary or secondary from the immediate catchment area only. This suggests the possibility of greater severity of the OCD sample relative to Panic disorder patients. All participants who met criteria for OCD were assessed for OCPD regardless of whether or not this was indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
0
24
1
2
Order By: Relevance
“…Indication for this hypothesis comes from studies that utilized structured interviews and DSM-IV criteria demonstrating cooccurrence rates that range between 23 and 45 % [21,49,[52][53][54]. Lower co-occurrence rates were found in (earlier) studies in which DSM-III, DSM-III-R or ICD-10-criteria were utilized as well as clinical judgments, questionnaires, and semistructured interviews for diagnostic assessment purposes [e.g.…”
Section: Ocpd and Obsessive-compulsive Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Indication for this hypothesis comes from studies that utilized structured interviews and DSM-IV criteria demonstrating cooccurrence rates that range between 23 and 45 % [21,49,[52][53][54]. Lower co-occurrence rates were found in (earlier) studies in which DSM-III, DSM-III-R or ICD-10-criteria were utilized as well as clinical judgments, questionnaires, and semistructured interviews for diagnostic assessment purposes [e.g.…”
Section: Ocpd and Obsessive-compulsive Disordermentioning
confidence: 99%
“…[55][56][57]. Further evidence for an overlap between OCD and OCPD originates from studies showing significantly higher cooccurrence rates between OCPD and OCD than between OCPD and the general population [21,22] or other mental disorders [52,58] (for contradictory findings, see Albert et al, 2004 [21]) (for more details, see Table 1). Even more evidence comes from studies demonstrating (significantly) higher comorbidity rates between OCPD and OCD than between other personality disorders and OCD [22,53,54,56,59,60].…”
Section: Ocpd and Obsessive-compulsive Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…This result is controversial. For example, co-occurring OCD and OCPD is sometimes associated with greater self-reported OCD severity [42,44], but there are a number of studies that do not support the notion that OCD with OCPD is a marker for OCD clinician-rated severity based on the Y-BOCS-SS total scores [11,45]. A possible explanation for this result is that OCD patients with comorbid OCPD might suffer less from their OC symptoms and may also report lower distress because of ego-syntonicity [46].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies have shown that patients with OCD and comorbid OCPD are characterized by an increased frequency of hoarding symptoms compared to noncomorbid OCD. 47,71 Conversely, the presence of hoarding symptoms in patients with OCD was found to be associated with an increased frequency of OCPD traits, 72 even when the hoarding criterion was removed from analysis, 73 suggesting an association does exist between OCD, hoarding symptoms, and the remaining OCPD criteria. It is noteworthy, however, that the ICD-10 definition of anankastic personality disorder does not include a hoarding criterion.…”
Section: Phenomenologymentioning
confidence: 98%